2008
DOI: 10.4161/pri.2.1.6297
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin fragmentation is implicated in 'free' copper deregulation of Alzheimer disease

Abstract: A dysfunction in copper homeostasis seems to occur in Alzheimer's disease (AD). We recently demonstrated that an excess of non-ceruloplasmin-copper (i.e., 'free' copper) correlates with the main functional and anatomical deficits as well as the cerebrospinal markers of the disease, thus suggesting that copper contributes to AD neurodegeneration. Aim of this study was to investigate the profile of serum ceruloplasmin isoforms immunoreactive protein in relation to copper dysfunction in AD. Twenty-five AD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 27 publications
2
33
0
3
Order By: Relevance
“…Since ceruloplasmin is a sulfur-containing protein, it is tempting to suggest that significant amounts of this molecule or its fragments can cross a compromised BBB in Skogholt disease, explaining the Cu-S-correlation found in the CSF. Interestingly, the concept 7 of Cu-containing ceruloplasmin fragments has been implicated in the pathogenesis of Alzheimer's disease [13]. This is consistent with the idea of low molecular weight nonalbumin non-IgG Cu-complexes playing a metal-carrying role in Skogholt disease.…”
Section: By What Mechanisms Are Iron and Copper Transferred From Bloosupporting
confidence: 73%
See 1 more Smart Citation
“…Since ceruloplasmin is a sulfur-containing protein, it is tempting to suggest that significant amounts of this molecule or its fragments can cross a compromised BBB in Skogholt disease, explaining the Cu-S-correlation found in the CSF. Interestingly, the concept 7 of Cu-containing ceruloplasmin fragments has been implicated in the pathogenesis of Alzheimer's disease [13]. This is consistent with the idea of low molecular weight nonalbumin non-IgG Cu-complexes playing a metal-carrying role in Skogholt disease.…”
Section: By What Mechanisms Are Iron and Copper Transferred From Bloosupporting
confidence: 73%
“…Copper has been found in significantly elevated concentrations in cerebrospinal fluid (CSF) from patients with amyotrophic lateral sclerosis [12]. Recent studies have also indicated a pathogenetic role for Cu in Alzheimer's disease [13][14][15][16], evident by the copper-enrichment of the amyloid-beta-peptide plaques in the nervous tissue of Alzheimer patients [17,18], and in Parkinson's disease, evident by the specific Cu catalyzed oxidation of synuclein in Parkinson patients [19]. To what extent metal dyshomeostasis or elevated nerve metal concentrations can precipitate demyelination is however still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In neurons, CP concentration was found to be unchanged in the brains of AD patients [13] and in our study the CP concentration in serum was the same as in the controls. In contrast other authors found raised CP concentration in the serum of AD patients [14,15], although Squitti et al (2005) later found fragments of CP proteolysis in the serum of AD patients, possibly indicating defective CP activity [16]. Considering these findings, it appears that CP concentration is normal or raised in AD although its activity seems to be lower.…”
Section: Alzheimer's Diseasementioning
confidence: 75%
“…These fragments may release some of their copper. It should be noted that Squitti et al 22 have observed abnormal fragmentation of Cp in serum of patients with AD.…”
Section: Discussionmentioning
confidence: 95%